The effects of copper and calcium ion supplementation on basal stem rot in oil palm (Elaeis guineensis). - Meon, Sariah; Ahmad Azmi, Nur Sabrina; Abdul Rahman, Zaharah (2012)
Ganoderma boninense the causal pathogen of Basal Stem Rot (BSR) disease is a white rot basidiomycetous fungus. The pathogen infects oil palm (Etaeis guineensis Jacq.) mainly through its roots and degrade the lignin component of wood leaving white cellulose exposed. The effects of copper and calcium nutrient supplementation on basal stem rot disease were evaluated in oil palm during a 8-month glasshouse study. Nutrients were supplemented when seedlings were 4 months old. Nutrient supplementation with copper at 2.0 mg/L and calcium at 4000 mg/L alone or in combination significantly reduced G. boninense infection in oil palm roots and bole tissues. The treated seedlings did not escape the disease, but it developed more gradually than in the untreated seedlings. The seedlings supplemented with a combination of calcium and copper remained free from any symptoms for a longer period and developed the disease at a later stage than' the controls. Supplementation with nutrients produced lignin-related enzymes, such as peroxidase (POD) and laccase, as well as hydrogen peroxide (H2O2). At 3 months after supplementation, the amount of H2O2 in tissues was lowest when treated with 2 mg/L of Cu or 4000 mg/L of Ca (181uM/L and 174uM/L, respectively). POD was significantly enhanced by Ca and Cu treatment with activity highest in tissues treated with 2 mg/L of Cu (11.3 U1mg) or 4000 mg/L of Ca (13.1 U/mg). Laccase activity in Cu- and Ca-treated tissues was significantly increased after supplementation. At 3 months, the laccase activity was the highest in tissues treated with 2 mg/L of Cu and 4000 mg/L of Ca (1.8 U/mg and 3.0 U/mg, respectively). The lignin content was the highest in tissues treated with 2 mg/L of Cu (152.9 mg/g) and 4000 mg/L of Ca (176.7 mg/g). Scanning electron microscopy analysis of Cu- and Ca-treated tissues revealed the cell walls between adjacent parenchyma cells to be the thickest 3 months after supplementation (5.55 um and 6.01 um, respectively). These findings suggested that copper and calcium supplementation can be used to reduce the severity of basal stem rot in oil palm.